Indicators, distinctive for women with different ovarian status and different responses streslimiting effect of bioactive water Naftussya SPA Truskavets’ - Barylyak, L G; Kruhliy, Yu Z; Zukow, W; Yanchiy, O R; Popovych, I L (Journal of Education, Health and Sport, 2015)
Barylyak L G, Kruhliy Yu Z, Zukow W, Yanchiy O R, Popovych I L. Indicators, distinctive for women with different ovarian status and different responses streslimiting effect of bioactive water Naftussya SPA Truskavets’. Journal of Education, Health and Sport. 2015;5(3):247-258. ISSN 2391-8306. DOI: 10.5281/zenodo.16398 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A247-258 https://pbn.nauka.gov.pl/works/550101 http://dx.doi.org/10.5281/zenodo.16398 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. INDICATORS, DISTINCTIVE FOR WOMEN WITH DIFFERENT OVARIAN STATUS AND DIFFERENT RESPONSES STRESLIMITING EFFECT OF BIOACTIVE WATER NAFTUSSYA SPA TRUSKAVETS’ L G Barylyak1,3, Yu Z Kruhliy1, W Zukow2, O R Yanchiy4, I L Popovych3 1JSC “Truskavets’kurort”, Truskavets’, Ukraine kuz2005@ukr.net 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl 3Laboratory of Balneology, OO Bohomolets’ Institute of Physiology, Truskavets’-Kyiv, Ukraine i.popovych@ukr.net 4Department of Medical Biology, OO Bohomolets’ National Medical University, Kyiv, Ukraine Summary The method of discriminant analysis revealed that the group of women with different ovarian status differ not only in the absence or presence echonegative or echopositive ovarian cysts, but the ovarian and uterine volume, prolactinemia level, pH of the skin, blood levels of the subpopulation of "active" T-lymphocytes, sympathetic tone and moda HRV, as well as the severity of weakness. It is shown that changes in neuro-hormonal stress index because of balneotherapy bioactive water Naftussya accompanied by characteristic groups of women with different ovarian status changes neuroendocrine (vegetative stress index, sympathetic tone, moda HRV, autonomic reactivity, thyrotropin, triiodothyronine, aldosterone) and immune (total white blood cell count, the relative content of "active" and theophylline sensitive T-lymphocytes, B-lymphocytes, natural killer cells) parameters, systolic blood pressure, skin pH, severity of weakness, headaches, puffiness, constipation and flatulence. Keywords: stress, ovarian, neuroendocrine, immune status, bioactive water Naftussya, Truskavets’.